A method of enhanced leaching of scandium from scandium-bearing silicate minerals

CN123005151APending Publication Date: 2026-10-30HUBEI GEOLOGY EXPERIMENTATION & RES INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611214200.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0009]针对现有技术的缺陷,本申请的目的在于提供一种从含钪硅酸盐矿物中强化浸出钪的方法,旨在解决现有技术从矿物结构稳定、化学性质惰性、含硅量高的硅酸盐矿物中提取钪存在的试剂消耗量大、提取效率低、硅胶影响严重、无法适应工业生产需求等的技术问题

Benefits of technology

(1)本发明针对工业上长期难以突破的钪提取难题,即从矿物结构稳定、化学性质惰性、含硅量高的硅酸盐矿物中提取钪,首次将“氯化钙高温焙烧活化”与“氟化钙助浸强化浸出”两个环节进行系统性耦合,形成“先焙烧破晶、后助浸溶出”的协同提钪工艺。氯化钙焙烧在高温下分解产生Cl2和HCl气体,从根本上破坏辉石、角闪石等载钪硅酸盐矿物的晶体结构,打开钪的释放通道;焙烧后的矿物晶格已产生大量缺陷和裂缝,使得后续浸出阶段氟化钙释放的F-离子能够更高效地作用于Si—O键,实现“靶向攻击”。两者在时序上形成“破晶→溶出”的分步协同,在机理上形成“热化学活化→化学强化浸出”的机制互补,产生了显著的协同效应。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123005151A_ABST
    Figure CN123005151A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of rare metal hydrometallurgy, and more particularly relates to a method for intensifying leaching of scandium from scandium-containing silicate minerals. In view of the technical problem that scandium is contained in pyroxene, hornblende and other silicate minerals, and the crystal structure is stable, leading to difficulty in acid leaching, the application provides a synergistic technical scheme of "calcium chloride roasting activation-fluoride calcium assisted leaching intensification leaching": scandium-containing minerals are mixed with calcium chloride, and then roasting is carried out at 800-900 DEG C, Cl2 and HCl gas generated by high-temperature decomposition of calcium chloride is used to destroy the crystal structure of silicate minerals, so that scandium wrapped in the crystal lattice is released and partially converted into soluble chloride; the roasting clinker is placed in a hydrochloric acid system again, and leaching is carried out with calcium fluoride as an assisted leaching agent, and fluoride ions further destroy the residual Si-O bond, so that efficient dissolution of scandium is realized. The process of the application is short and the operation is controllable, and is suitable for scandium recovery of gabbro type low-grade magnetite and similar scandium-containing silicate mineral resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of rare metal hydrometallurgy technology, and more specifically, relates to a method for enhanced leaching of scandium from scandium-containing silicate minerals. Background Technology

[0002] Scandium (Sc) is a typical rare lithophile element, with an average abundance of only 22 g / t in the Earth's crust, rarely forming independent rich aggregates. Currently, over 800 known scandium-bearing minerals have been identified, which can be categorized into three main types: First, independent minerals, such as scandium-yttrium, scandium hydrophosphorite, beryllium-scandium, and scandium-zirconite, which typically do not constitute ore bodies of industrial significance. Second, isomorphous scandium-bearing minerals, where the vast majority of scandium is dispersed in silicate, oxide, and sulfide minerals in isomorphous forms. Third, ion-adsorbed scandium-bearing minerals, which, under specific geological conditions, undergo long-term and intense chemical weathering of the scandium-bearing bedrock, leading to the decomposition of primary minerals. During this process, Sc³ is released from the crystal lattice. + Ions, in the form of ions or hydrated ions, are adsorbed by secondary minerals in the weathering crust. The main adsorption carriers are clay minerals and iron / aluminum oxide-hydroxide.

[0003] Different extraction strategies exist for scandium resources in different occurrence forms. The core idea is to first release scandium from the mineral in which it is found into the liquid phase, and then separate and purify it through extraction, ion exchange, and other methods. Currently available extraction methods mainly include: For ion-adsorbed scandium, such as scandium-bearing minerals in kaolinite, illite, montmorillonite, goethite, hematite, limonite, and certain bauxite deposits, this form of scandium has the weakest binding force and is relatively easy to extract. The process is highly similar to the extraction process for ion-adsorbed rare earth minerals. Using an electrolyte solution as the leaching agent, Sc³ adsorbed on the surface of clay minerals is extracted through ion exchange. + The scandium is displaced into the solution to form a scandium-containing leachate. This process is relatively mild and does not damage the mineral lattice.

[0004] The recycling process for associated scandium varies greatly depending on the associated substance and the smelting process. It is mainly recovered through by-products of the smelting process (such as titanium dioxide waste acid, chlorinated dust, red mud, etc.).

[0005] Scandium found in silicate minerals presents significantly increased extraction challenges, leading researchers to develop various technological approaches. The core objective of these technologies is consistent: to disrupt the crystal structure of silicate minerals, releasing scandium into soluble ions or compounds. Currently, mainstream technologies can be categorized into pyrometallurgical-hydrometallurgical combined processes and high-pressure hydrometallurgical processes. Existing methods primarily include: alkaline roasting-acid leaching, where scandium-containing silicate minerals are mixed with alkaline additives (such as sodium carbonate, sodium hydroxide, and limestone) and roasted at high temperatures. At these temperatures, the alkaline additives react with the silicates, disrupting their network structure and generating acid-soluble silicates and aluminates, while scandium is also converted to an acid-soluble state. The roasted clinker is then acid-leached to efficiently dissolve the scandium; sulfation roasting-water leaching, where the ore is mixed with concentrated sulfuric acid or sulfates and roasted at relatively low temperatures (typically 200-600℃). Sulfuric acid converts metallic elements (including scandium) in minerals into water-soluble sulfates, and the roasted products can be directly leached with water or dilute acid. High-pressure acid leaching is a hydrometallurgical technique that directly decomposes minerals with acid under high temperature and pressure conditions. It is considered an effective method for processing complex oxide / silicate ores such as laterite nickel ore and has been widely studied in recent years for extracting scandium from red mud and scandium-bearing ores. Chlorination is a metallurgical technique that uses chlorine gas or solid chlorinating agents to convert metallic components in minerals into gaseous or soluble chlorides under high temperature conditions. For scandium extraction, this technology mainly includes two branches: fluidized bed chlorination and chlorination roasting. In fluidized bed chlorination, scandium is chlorinated at high temperature to generate scandium chloride with a lower boiling point, which volatilizes into the gas phase and condenses during subsequent flue gas cooling, being captured in chlorinated dust for recovery. Chlorination roasting involves adding a solid chlorinating agent to achieve chlorination decomposition of the mineral at a lower temperature, forming easily leached scandium chloride.

[0006] The extraction of scandium from silicate minerals is extremely difficult primarily because scandium is isomorphously embedded in the stable crystal lattice of silicate minerals. Silicate minerals are structurally stable and chemically inert, making effective extraction difficult under conventional acid leaching conditions. The extraction difficulty varies considerably among different silicate minerals, mainly depending on the specific coordination position and substitution mode of scandium within the mineral lattice, as well as the mineral's own crystal chemical stability. For example, scandium isomorphously incorporated into the pyroxene / amphibole lattice, primarily occupying the M1 / M2 sites (pyroxene) or M1-M4 sites (amphibole). The significant differences in stability at different positions lead to varying degrees of leaching difficulty. Furthermore, the chemical stability of different silicate minerals varies considerably; for instance, aegirine contains a large amount of Fe³⁺. + During reducing roasting or acid leaching, Fe³ + Reduced to Fe² + At this time, lattice expansion generates defects, Sc³ +Because it is easily released, nephrite leaching is less difficult. However, when processing raw materials with high silicon content, both alkaline roasting-acid leaching and sulfation roasting-water leaching methods face a common technical challenge—silica gel formation. When the silicon framework in scandium-containing silicate minerals is largely destroyed during roasting-leaching, silicon enters the solution as soluble silicic acid. When the SiO2 concentration in the solution exceeds approximately 1 g / L, under acidic conditions, silicic acid molecules undergo polymerization and condensation reactions, gradually forming silicic acid sols and even gels with a three-dimensional network structure. Silica gel has extremely strong water absorption, swelling, and gelling properties, rapidly forming a dense, highly viscous gel layer on the surface of filter cloth or filter cartridges, making solid-liquid separation extremely difficult. Simultaneously, the three-dimensional network structure of the silicic acid gel physically encapsulates and adsorbs a large number of dissolved metal ions during formation, causing valuable scandium to be carried into the waste residue, reducing the leaching rate. Silica gel can also coat the surface of unreacted mineral particles, forming a diffusion barrier that hinders the contact between new acidic leaching agents and the interior of the minerals, leading to a decrease or even stagnation in the leaching reaction rate.

[0007] While both chlorination and leaching aids-enhanced leaching techniques have their merits, they also have significant limitations. Xu Yanhui et al.'s paper, "Extraction of Scandium from Niobium Tailings in Bayan Obo by Calcium Chloride Roasting and Hydrochloric Acid Decomposition," uses a calcium chloride roasting followed by acid leaching to extract scandium. Ge Yangyang et al.'s paper, "Extraction of Scandium from Vanadium-Titanium Magnetite Tailings by Two-Stage Acid Leaching with Fluorine-Containing Auxiliaries," uses calcium fluoride and acid extraction. Although both methods achieve scandium extraction rates exceeding 90%, the former requires 60% calcium chloride and the latter 25% calcium fluoride, with a leaching time of 7 hours. Such high reagent usage and a 7-hour extraction time result in excessively high costs and low efficiency, making them unsuitable for industrial-scale scandium extraction.

[0008] In summary, there is currently a lack of a low-cost, high-efficiency process suitable for industrial-scale production that can effectively disrupt the stable lattice structure of silicates and reduce the influence of silica gel for efficient extraction of scandium from silicate minerals with stable mineral structure, inert chemical properties, and high silicon content. Summary of the Invention

[0009] In view of the shortcomings of the prior art, the purpose of this application is to provide a method for enhanced leaching of scandium from scandium-containing silicate minerals, aiming to solve the technical problems of high reagent consumption, low extraction efficiency, serious influence of silica gel, and inability to meet the needs of industrial production in the extraction of scandium from silicate minerals with stable mineral structure, inert chemical properties and high silicon content.

[0010] To achieve the above objectives, in a first aspect, this application provides a method for synergistically enhancing the leaching of scandium from scandium-containing silicate minerals, comprising the following steps: Scandium-containing silicate minerals are crushed, ground, and magnetically separated to obtain iron concentrate and scandium-containing tailings; Scandium-containing tailings are mixed with calcium chloride and roasted and activated at 800~950℃ to obtain roasted slag; The roasted residue was placed in an aqueous solution of inorganic acid and leached with calcium fluoride as a leaching aid to obtain a scandium-containing leachate.

[0011] Preferably, the calcium chloride is activated by calcination at a temperature of 850-900°C for 1-2 hours.

[0012] Preferably, the amount of calcium chloride added is 20% to 40% of the mass of the scandium-containing tailings, and more preferably 20% to 30%.

[0013] Preferably, the calcined residue is placed in an inorganic acid aqueous solution and leached with calcium fluoride as a leaching aid. Specifically, the calcined residue is mixed with the inorganic acid aqueous solution at a solid-liquid ratio of 6:1 to 10:1, and then calcium fluoride is added as a leaching aid for leaching.

[0014] Preferably, the inorganic acid aqueous solution is a hydrochloric acid aqueous solution, and the concentration of the hydrochloric acid aqueous solution is from 13.5 wt% to 22.5 wt%.

[0015] Preferably, the conditions for calcium fluoride-assisted acid leaching are as follows: the amount of calcium fluoride added is 8% to 15% of the mass of the scandium-containing tailings, more preferably 10-15%; the leaching temperature is 80 to 95°C, and the leaching time is 1.5 to 2 hours.

[0016] Overall, the technical solutions conceived in this application have the following beneficial effects compared with the prior art: (1) This invention addresses the long-standing industrial challenge of scandium extraction, specifically the extraction of scandium from silicate minerals with stable mineral structures, inert chemical properties, and high silicon content. For the first time, it systematically couples the two steps of "high-temperature roasting activation with calcium chloride" and "calcium fluoride-assisted leaching to enhance extraction," forming a synergistic scandium extraction process of "first roasting to break the crystals, then assisted leaching." Calcium chloride roasting decomposes at high temperatures to produce Cl2 and HCl gases, fundamentally destroying the crystal structure of scandium-loaded silicate minerals such as pyroxene and amphibole, opening the release channels for scandium. The roasted mineral lattice already contains numerous defects and cracks, making it difficult for calcium fluoride to release F2 during the subsequent leaching stage. - Ions can act on Si-O bonds more efficiently, achieving "targeted attack". The two form a stepwise synergy of "crystal breaking → dissolution" in terms of time sequence, and a complementary mechanism of "thermochemical activation → chemically enhanced leaching" in terms of mechanism, producing a significant synergistic effect.

[0017] (2) During the calcium chloride roasting process, calcium chloride reacts with some of the SiO2 in the mineral to form stable calcium silicate, which fixes silicon in the roasting slag in a solid form, instead of converting silicon into soluble silicates and entering the liquid phase as in the alkali fusion method. This greatly reduces the amount of soluble silicon in the liquid phase during subsequent acid leaching, thus avoiding the formation of silica gel from the source. This eliminates the slurry viscosity, filtration difficulties and scandium adsorption loss caused by silica gel, and also eliminates the desilication pretreatment step.

[0018] (3) The system optimized the key process parameters of calcium chloride roasting and determined the optimal range of conditions for achieving efficient activation. This ensured the full destruction of the mineral lattice and avoided the increase in energy consumption and secondary coating caused by over-roasting, thus creating the best mineral surface state for subsequent calcium fluoride leaching.

[0019] (4) Based on the phase composition and structural characteristics of the minerals after calcium chloride roasting, the process parameters of calcium fluoride-assisted acid leaching were optimized, achieving efficient dissolution of scandium from the roasting product. Calcium fluoride continuously releases F in the hydrochloric acid system. - The ions, in synergy with the lattice defects generated during calcination, significantly reduce the activation energy of scandium leaching, which is superior to the traditional acid leaching process. Attached Figure Description

[0020] Figure 1 This is a process flow diagram of the method for synergistically enhancing the leaching of scandium from scandium-containing silicate minerals according to the present invention.

[0021] Figure 2 The graph shows the experimental results of calcium chloride roasting temperature conditions in Example 1 of the present invention (horizontal axis: roasting temperature / ℃, vertical axis: scandium leaching rate / %).

[0022] Figure 3 The graph shows the experimental results of calcium chloride dosage conditions in Example 1 of the present invention (horizontal axis: calcium chloride dosage / %, vertical axis: scandium leaching rate / %).

[0023] Figure 4 The graph shows the test results of the calcium fluoride leaching aid dosage conditions in Example 1 of the present invention (horizontal axis: CaF2 dosage / %, vertical axis: scandium leaching rate / %).

[0024] Figure 5 The graph shows the test results of leaching temperature conditions in Example 1 of the present invention (horizontal axis: leaching temperature / ℃, vertical axis: scandium leaching rate / %).

[0025] Figure 6 The graph shows the test results of leaching time conditions in Example 1 of the present invention (horizontal axis: leaching time / h, vertical axis: scandium leaching rate / %).

[0026] Figure 7 This is a bar chart comparing the scandium leaching rate under different process conditions in Examples 1, 3, and 5 of this invention.

[0027] Figure 8 Contents (a), (b), and (c) are scanning electron microscope (SEM) images of magnetic separation tailings, SEM images of chlorinated roasted tailings, and SEM images of leaching tailings, respectively. Detailed Implementation

[0028] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0029] To address the technical problems of existing technologies for extracting scandium from scandium-containing silicate minerals, which are characterized by stable mineral structure, inert chemical properties, and high silicon content, such as high reagent consumption, low extraction efficiency, severe influence of silica gel, and inability to meet industrial production requirements, this invention provides a method for synergistically enhancing the leaching of scandium from scandium-containing silicate minerals, comprising the following steps: Scandium-containing silicate minerals are crushed, ground, and magnetically separated to obtain iron concentrate and scandium-containing tailings; Scandium-containing tailings are mixed with calcium chloride and roasted and activated at 800~950℃ to obtain roasted slag; The roasted residue was placed in an aqueous solution of inorganic acid and leached with calcium fluoride as a leaching aid to obtain a scandium-containing leachate.

[0030] In some embodiments, the -0.074 mm particle size accounts for 80% to 87% of the mineral powder after crushing and grinding the scandium silicate mineral. The magnetic field strength used in the magnetic separation is 20 kA·m to 120 kA·m, preferably 20 kA·m to 60 kA·m; the iron concentrate accounts for 15% to 20% of the mass of the scandium silicate mineral.

[0031] In some embodiments, the scandium-bearing silicate mineral is one or more of diopside, bronzite, and amphibole, with scandium occurring isomorphously in the silicate mineral lattice. The scandium content in the scandium-bearing tailings is from 16 μg / g to 100 μg / g.

[0032] In a preferred embodiment, the calcium chloride is roasted and activated at a temperature of 850-900°C for 1-2 hours. The amount of calcium chloride added is 20%-40% of the mass of the scandium-containing tailings, taking into account both extraction efficiency and economy, and more preferably 20%-30%.

[0033] In some embodiments, the calcined residue is placed in an aqueous inorganic acid solution and leached with calcium fluoride as a leaching aid. Specifically, the calcined residue is mixed with the aqueous inorganic acid solution at a solid-liquid ratio of 6:1 to 10:1, and then calcium fluoride is added as a leaching aid for leaching. If the liquid-solid ratio is too low, the leaching rate will decrease; if it is too high, the scandium concentration in the leachate will decrease, affecting subsequent impurity removal and extraction.

[0034] In some embodiments, the inorganic acid aqueous solution is a hydrochloric acid aqueous solution with a concentration of 13.5 wt% to 22.5 wt%. During the experiment, persulfate aqueous solution, hydrochloric acid aqueous solution, and nitric acid aqueous solution systems were used to leach the roasted residue. The leaching effects of hydrochloric acid and nitric acid aqueous solutions were similar (both above 80%), while the leaching effect of sulfuric acid aqueous solution was poor, with a leaching rate of only 30-40%. This may be because calcium ions and sulfate ions combine to form slightly soluble calcium sulfate, hindering leaching. Since calcium chloride was added during the preceding roasting process, chloride ions were already introduced. In subsequent processes, calcium and chloride ions in the leaching solution will be recovered as calcium chloride. Therefore, it is not desirable to introduce new anions (nitrate ions, sulfate ions) during the leaching process, as this would increase the difficulty of calcium chloride recovery. Hydrochloric acid aqueous solution is preferred, and the recovered calcium chloride can be reused in chlorination roasting.

[0035] In some embodiments, the conditions for calcium fluoride-assisted acid leaching are as follows: the amount of calcium fluoride added is 8% to 15% of the mass of the scandium-containing tailings, more preferably 10 to 15%; the leaching temperature is 80 to 95°C, and the leaching time is 1.5 to 2 hours.

[0036] This invention employs a sequential synergistic enhancement system consisting of calcium chloride roasting and calcium fluoride leaching aids, first roasting to break the crystal structure and then leaching to dissolve the scandium. The synergistic application of calcium chloride roasting and calcium fluoride leaching aids in the leaching of scandium-containing silicate minerals involves: firstly, high-temperature roasting with calcium chloride disrupts the crystal structure of the scandium-bearing silicate minerals, opening the initial release channel for scandium; then, calcium fluoride releases F in a hydrochloric acid system. - Ions attack the residual Si-O bonds in the calcined minerals, achieving deep dissolution of scandium. The two processes work in a stepwise synergistic manner, "crystal breaking → dissolution," and mechanistically, "thermochemical activation → chemically enhanced leaching," complementing each other; neither is dispensable. The synergistic effect of calcium chloride calcination and calcium fluoride-assisted leaching significantly increases the scandium leaching rate compared to calcium chloride calcination or calcium fluoride-assisted leaching alone. Furthermore, it achieves a higher scandium leaching rate with lower reagent dosage and within the same or shorter timeframe, while simultaneously reducing the adverse effects of silica gel during the leaching process.

[0037] At high temperatures of 800-900℃, calcium chloride undergoes thermal decomposition, producing Cl2 and HCl gases. These reactive gases react with scandium-loaded silicate minerals (pyroxene, amphibole): HCl and Cl2 can penetrate into the interior of the mineral particles, causing chlorination of metal oxides and "pulling" metal cations out of the crystal lattice, thus disrupting the silicate crystal structure. After the lattice is disrupted, when Ca, Mg, and Fe ions connecting the silicon-oxygen tetrahedra are chlorinated and detached from the lattice, the silicon-oxygen tetrahedral framework originally connected by these cations loses its structural support, resulting in macroscopic collapse, amorphization, and the formation of cracks and defects. During subsequent leaching, calcium fluoride releases F... - The ions have a strong affinity for silicon and can attack the Si-O bonds in minerals after calcium chloride roasting: after pre-activation by calcium chloride roasting, the mineral lattice has generated a large number of defects and microcracks, F - Ions penetrate more easily into the interior of minerals; F- and Si 4+ Combine to form stable SiF6 2- The complex ions further promote the breaking of Si-O bonds, allowing the scandium encapsulated in the silicate structure to be completely released.

[0038] The embodiments of the present invention are implemented under the premise of the technical solution of the present invention, and detailed implementation methods and processes are given. However, the protection scope of the present invention is not limited to the following embodiments. The process parameters in the following embodiments that do not specify specific conditions are generally in accordance with conventional conditions.

[0039] The endpoints and any values ​​of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.

[0040] Example 1 (a) Raw materials The test sample was taken from the Shuguang Iron Mine in Tangwang County, Heilongjiang Province, and was a low-grade magnetite ore of the gabbro type. The chemical composition of the raw ore (wt%) was: TFe 12.81%, Sc 49.13 μg / g, Co 65.5 μg / g, SiO2 43.93%, Al2O3 16.59%, CaO 12.83%, and MgO 7.08%. The main constituent minerals were plagioclase (38.99%), pyroxene (24.49%), amphibole (16.90%), and magnetite (10.08%). Sc was mainly found in pyroxene (58.71%), followed by amphibole (28.17%), while the Sc content in magnetite was extremely low (0.87%). The pyroxene consisted of two types: diopside and enstatite, and the amphibole was common amphibole.

[0041] (II) Implementation Steps like Figure 1 As shown, the extraction of scandium from the above minerals includes the following steps: Step 1: Grinding After the raw ore is crushed, it is ground on an XMQ-240×90 conical ball mill with a grinding concentration of 50%. The grinding time is controlled so that the -0.074mm particle size accounts for 80%.

[0042] Step 2: Weak magnetic selection pre-enrichment After grinding, samples were subjected to weak magnetic separation under a magnetic field strength of 47.75 kA·m. The iron concentrate yield was 15.86%, iron grade was 53.55%, and iron recovery was 66.30%. The tailings yield was 84.14%, scandium grade was 55.83 μg / g, and scandium recovery was 95.61%. Scandium was efficiently enriched in the tailings during the weak magnetic separation process.

[0043] Step 3: Calcium chloride calcination activation Take 20g of weak magnetic separation tailings, add 6g of anhydrous calcium chloride (the amount added is 30% of the mass of weak magnetic separation tailings), mix thoroughly, place in a corundum crucible, and calcine at 850℃ for 2 hours in a box-type resistance furnace.

[0044] The proposed activation mechanism of calcium chloride roasting is as follows: Under high temperature conditions of 850℃, calcium chloride undergoes a thermal decomposition reaction, producing Cl2 and HCl gases. These active gases react with scandium-loaded silicate minerals (pyroxene, amphibole): HCl and Cl2 can penetrate into the interior of mineral particles, causing chlorination of metal oxides, which "pull" the metal cations out of the crystal lattice and destroy the silicate crystal structure. After the crystal lattice is destroyed, when the Ca, Mg, Fe and other ions that connect the silicon-oxygen tetrahedra are chlorinated and detached from the crystal lattice, the silicon-oxygen tetrahedral framework that was originally connected by these cations loses its structural support, resulting in macroscopic collapse, amorphization, and the generation of cracks and defects.

[0045] After calcination, the material was naturally cooled to room temperature to obtain calcined clinker. This clinker is characterized by a loose crystal lattice and high surface activity, which creates favorable kinetic conditions for subsequent calcium fluoride leaching.

[0046] Step 4: Calcium fluoride-assisted acid leaching Place the roasted residue in a 250mL three-necked flask, add 18wt% hydrochloric acid solution (liquid-solid ratio 8:1, i.e., 160mL hydrochloric acid solution), add calcium fluoride (the amount added is 12% of the mass of scandium tailings, i.e. 2.4g), and stir and leach for 2 hours under a 90℃ water bath heating condition.

[0047] The hypothetical synergistic mechanism of calcium fluoride leaching is as follows: In the hydrochloric acid system, calcium fluoride reacts with hydrochloric acid to slowly release F. - Ions: CaF₂ + 2HCl → CaCl₂ + 2HF Released F - The ions have a strong affinity for silicon and can attack the residual Si-O bonds in minerals after calcium chloride roasting: After pre-activation by calcium chloride roasting, the mineral lattice has developed numerous defects and microcracks. - Ions can penetrate into the interior of minerals more easily; F - With Si 4+ Combine to form stable SiF6² - Complex ions further promote the breaking of Si-O bonds, allowing the scandium encapsulated in the silicate structure to be completely released; Released Sc³ + It is then dissolved by hydrochloric acid to form ScCl3, which enters the solution.

[0048] The synergistic mechanism of calcium chloride roasting and calcium fluoride leaching can be summarized as a "two-step progression": Step 1 (Calcination and Crystal Breakage): The Cl2 and HCl produced by the high-temperature decomposition of calcium chloride disrupt the main crystal lattice of pyroxene / amphibole, opening the initial release channel for scandium, while simultaneously converting some scandium into soluble chlorides; Step 2 (Assisted Leaching): The F released by calcium fluoride... - Ions utilize lattice defects generated during calcination to efficiently attack residual Si-O bonds, achieving deep dissolution of scandium. The two steps form a synergistic and complementary temporal process of "thermochemical activation → chemically enhanced leaching," neither of which can be omitted.

[0049] After leaching, vacuum filtration was performed to obtain a scandium-containing leachate and leaching residue. The scandium leaching rate was measured to be 82.81%.

[0050] Example 2 The difference between this embodiment and Embodiment 1 lies in the different process parameters during the calcium chloride roasting stage, in order to verify the applicable conditions of the synergistic process.

[0051] Steps 1 and 2: Same as in Example 1.

[0052] Step 3 (calcination and activation of calcium chloride): Take 20g of weak magnetic separation tailings, add 4g of calcium chloride (the amount added is 20% of the mass of the tailings), mix thoroughly, and then calcine at 850℃ for 2 hours.

[0053] Step 4: Same as Example 1 (calcium fluoride addition 12%, hydrochloric acid concentration 18%, liquid-solid ratio 8:1, 90℃, 2h).

[0054] Results: The scandium leaching rate was 75.52%, lower than 82.81% in Example 1, but still significantly better than the effects of calcium chloride roasting alone (Comparative Example 1) or calcium fluoride leaching aid alone (Comparative Example 2). This result indicates that the synergistic process can enhance leaching over a wide range of parameters.

[0055] Example 3 The difference between this embodiment and Embodiment 1 lies in the amount of calcium fluoride used in the leaching stage. This is to verify the applicable conditions of the synergistic process.

[0056] Steps 1 to 3: Same as in Example 1.

[0057] Step 4 (Calcium fluoride-assisted acid leaching): The amount of calcium fluoride added is 8% (i.e., 1.6g) of the mass of scandium-containing tailings, and other conditions are the same as in Example 1 (hydrochloric acid concentration 18%, liquid-to-solid ratio 8:1, 90℃, 2h).

[0058] Results: The scandium leaching rate was 71.30%, lower than 82.81% in Example 1, but still significantly better than the effects of calcium chloride roasting alone (Comparative Example 1) or calcium fluoride leaching aid alone (Comparative Example 2). This result indicates that the synergistic process can enhance leaching over a wide range of parameters.

[0059] Example 5 The difference between this embodiment and Embodiment 1 is the leaching temperature.

[0060] Steps 1 to 3: Same as in Example 1.

[0061] Step 4 (Calcium fluoride-assisted acid leaching): The leaching temperature is 80℃, and other conditions are the same as in Example 1 (hydrochloric acid concentration 18%, liquid-to-solid ratio 8:1, calcium fluoride 12%, 2h).

[0062] Results: Scandium leaching rate was 76.66%. This indicates that synergistic leaching can achieve good results within the temperature range of 80-90℃.

[0063] from Figure 2 , Figure 3 , Figure 4 , Figure 5 and Figure 6It can be seen that in the calcium chloride roasting activation-calcined fluoride-assisted leaching scandium extraction process, the calcium chloride roasting activation temperature is 800-950℃, more preferably 850-900℃; the calcium chloride dosage can be 20wt%-40wt%, more preferably 20-30wt%, and further increasing the dosage will actually decrease the scandium leaching rate; in the calcium chloride roasting activation-calcined fluoride-assisted leaching co-extraction scandium extraction process of this application, the calcium fluoride dosage is not necessarily better the higher it is, the preferred calcium chloride dosage range is 8%~15%, more preferably 10-15%; the preferred calcium fluoride-assisted leaching temperature is 80-95℃; in the co-extraction process of this application, in the hydrochloric acid aqueous solution leaching and calcium fluoride-assisted leaching steps, after the leaching time exceeds 2 hours, the leaching rate no longer changes, so the preferred leaching time is 1.5-2 hours.

[0064] Comparative Example 1 The difference between this embodiment and Embodiment 1 is that calcium fluoride is not added during the leaching stage, in order to verify the applicable conditions of the synergistic process.

[0065] Steps 1 to 3: Same as in Example 1 Step 4: The roasted residue was directly leached with 18% hydrochloric acid (without adding calcium fluoride), with a liquid-to-solid ratio of 8:1, at 90°C, for 4 hours (the leaching time was twice that of Example 1 to ensure a complete reaction).

[0066] Results: The scandium leaching rate was only 33.83%. This indicates that without the synergistic effect of calcium fluoride leaching, efficient scandium leaching cannot be achieved by calcium chloride roasting alone, and the leaching rate is much lower than that in Example 1.

[0067] Comparative Example 2 The difference between this embodiment and Embodiment 1 is that calcium chloride is not added during the roasting stage, in order to verify the applicable conditions of the synergistic process.

[0068] Steps 1 and 2: Same as in Example 1.

[0069] Step 3: Take 20g of weak magnetic separation tailings and roast it directly at 850℃ for 2 hours.

[0070] Step 4: Same as Example 1, but with leaching time extended by 2 hours (calcium fluoride addition 12%, hydrochloric acid concentration 18%, liquid-to-solid ratio 8:1, 90°C, 2 hours).

[0071] Results: Scandium leaching rate was 36.15%. This indicates that without activation by calcium chloride roasting, calcium fluoride alone cannot effectively destroy the complete crystal structure of pyroxene and amphibole, making it difficult for scandium to dissolve completely.

[0072] Figure 7Comparing the scandium extraction rates in Example 1 (calcium chloride roasting activation-calcium fluoride leaching synergistic extraction), Comparative Example 1 (calcium chloride roasting activation-acid leaching extraction alone), and Comparative Example 2 (calcium chloride roasting activation-calcium fluoride leaching process without adding calcium chloride), it can be seen that, under the condition that other conditions remain unchanged, first using calcium chloride activation roasting, and then using calcium fluoride leaching in the hydrochloric acid system, the scandium extraction rate is unexpectedly improved, indicating that there is indeed a synergistic effect between the calcium chloride activation roasting and calcium fluoride leaching processes.

[0073] Figure 8 Contents (a), (b), and (c) are scanning electron microscope (SEM) images of magnetic separation tailings, SEM images after chlorination roasting, and SEM images after leaching, respectively. The comparison shows that the magnetic separation tailings particles have a dense and smooth surface; after roasting, numerous grooves and pores are formed on the mineral surface, and the crystal structure is destroyed; after leaching, the soluble components are fully dissolved, and the structure of the remaining solid particles tends to be stable. These microscopic morphological changes confirm that calcium chloride roasting pretreatment can improve the mineral reactivity, enabling efficient extraction of the target components in conjunction with subsequent calcium fluoride leaching.

[0074] Comparative Example 3 This comparative example uses an alkali fusion-water washing-acid leaching process.

[0075] Steps 1 and 2: Same as in Example 1.

[0076] Step 3: Take 20g of weak magnetic separation tailings and add 9g of sodium carbonate (45% of the sample mass) and mix thoroughly. Roast at 850℃ for 2 hours.

[0077] Step 4: Wash the calcined product with 200 mL of water for 15 min, and filter to separate. Repeat the washing process several times until the filtrate is neutral.

[0078] Step 5: Add the water-washed residue to an 18% hydrochloric acid solution and leach for 4 hours at a liquid-to-solid ratio of 8:1 (160mL:20g) and a temperature of 90℃.

[0079] Results: Scandium leaching rate was 47.97%. This indicates that alkali slag may easily generate silica gel during acid leaching, which can encapsulate the target mineral, resulting in a low leaching rate.

[0080] Comparative Example 4 This comparative example uses a sulfuric acid aging-acid leaching process.

[0081] Steps 1-2: Same as in Example 1.

[0082] Step 3: Take 20g of weak magnetic separation tailings sample and add 100% sulfuric acid (20g) relative to the sample mass. Mix thoroughly and calcine at 260℃ for 2h.

[0083] Step 4: Add deionized water to the roasted product and leach for 4 hours at a liquid-to-solid ratio of 8:1 (160mL:20g) and a temperature of 90℃.

[0084] Results: The leachate and leaching residue were difficult to filter and could not be separated at all. This indicates that sulfuric acid aging may also easily generate a large amount of silica gel when treating high-silica minerals, leading to difficulties in subsequent solid-liquid separation.

[0085] Comparative Example 5 The rest is the same as Comparative Example 1, except that 8g of anhydrous calcium chloride (40% of the mass of the weak magnetic separation tailings) is added to the calcium chloride roasting and activation step in step 3.

[0086] Results: The scandium leaching rate was 32.07%. This indicates that even increasing the amount of calcium chloride calcination aid could not improve the scandium leaching rate without the addition of calcium fluoride leaching aid.

[0087] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. A method for synergistically enhancing the leaching of scandium from scandium-containing silicate minerals, characterized in that, Includes the following steps: Scandium-containing silicate minerals are crushed, ground, and magnetically separated to obtain iron concentrate and scandium-containing tailings; Scandium-containing tailings are mixed with calcium chloride and roasted and activated at 800~950℃ to obtain roasted slag; The roasted residue was placed in an aqueous solution of inorganic acid and leached with calcium fluoride as a leaching aid to obtain a scandium-containing leachate.

2. The method as described in claim 1, characterized in that, The mineral powder obtained after crushing and grinding the scandium silicate mineral contains 80% to 87% particles of -0.074 mm size.

3. The method as described in claim 1, characterized in that, The magnetic separation uses a magnetic field strength of 20 kA·m to 120 kA·m; the iron concentrate accounts for 15% to 20% of the mass of the scandium-containing silicate minerals.

4. The method according to claim 1, characterized in that, The scandium-containing silicate mineral is one or more of diopside, bronzite, and amphibole, with scandium occurring in the silicate mineral lattice in an isomorphous manner.

5. The method according to claim 1, characterized in that, The scandium content in the scandium-containing tailings is from 16 μg / g to 100 μg / g.

6. The method as described in claim 1, characterized in that, The calcium chloride is activated by roasting at a temperature of 850~900℃ for 1~2 hours.

7. The method as described in claim 1, characterized in that, The amount of calcium chloride added is 20% to 40% of the mass of the scandium-containing tailings, preferably 20% to 30%.

8. The method as described in claim 1, characterized in that, The calcined residue was placed in an inorganic acid aqueous solution and leached with calcium fluoride as an auxiliary leaching agent. Specifically, the calcined residue was mixed with the inorganic acid aqueous solution at a solid-liquid ratio of 6:1 to 10:1, and then calcium fluoride was added as an auxiliary leaching agent for leaching.

9. The method according to claim 8, characterized in that, The inorganic acid aqueous solution is a hydrochloric acid aqueous solution, and the concentration of the hydrochloric acid aqueous solution is from 13.5 wt% to 22.5 wt%.

10. The method according to claim 4, characterized in that, The conditions for calcium fluoride-assisted acid leaching are as follows: the amount of calcium fluoride added is 8% to 15% of the mass of the scandium-containing tailings; the leaching temperature is 80 to 95°C; and the leaching time is 1.5 to 2 hours.